Los encuentros entre México y los Estados Unidos en Spanglish y Los tres entierros de Melquiades Estrada. - Manickam, Samuel (2012)
In this article the author carries out a comparative analysis of the representation of the Mexican migrant worker in two recent Hollywood films, Spanglish and The Three Burials of Melquiades Estrada. Aspects such as the main characters, the Mexican-American relationship and the bicultural-bilingual experience, among others will be discussed.